Analisis Pendekatan Humanistik Rogers Dalam Penanganan Kasus Perundungan Di Sekolah: Kajian Pustaka 2019–2024 - Cahaya Murti, Putri; lestari, Lidia; Qudratullah, Qudratullah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the application of Carl Rogers' humanistic approach in handling bullying cases in schools through a literature review of relevant studies from 2019 to 2024. Rogers' humanistic approach emphasizes respecting individuals as active subjects who have the potential for self-actualization and psychological needs that must be met to create a conducive and safe learning environment. The literature review method is used to examine various empirical studies and theories on the implementation of the humanistic approach in the context of school guidance and counseling to reduce bullying behavior. The study results indicate that the application of humanistic principles such as empathy, unconditional acceptance, and effective communication can enhance the self-awareness of both bullying perpetrators and victims, as well as facilitate positive behavioral changes within the school environment. The practical implication is the importance of involving teachers and counselors as humanistic facilitators in order to create an inclusive school atmosphere that supports students' character development. This study recommends the development of humanistic-based intervention programs as a preventive measure in addressing bullying in education.